Exhibitionary Acts of Political Imagination - Gheorghe, Cătălin; Wilson, Mick (Iaşi : Editura Artes, 2021)
Cătălin Gheorghe and Mick Wilson – Exhibitionary Acts of Political Imagination. Introduction ; Galit Eilat – The Transparent Museum through the Looking Glass ; Vasıf Kortun and Merve Elveren – What Do We Do Now? ; The space of the exhibition as a space of political potential – A Conversation with Cosmin Costinaș ; Marco Scotini – Not a Just Exhibition, But Just an Exhibition. The Case of Disobedience Archive ; Nick Aikens – Approaching Research-Exhibition Practices ; Carolina Rito – Infrastructures of the Exhibitionary ; Simon Sheikh – The Problem Is Not To Make Political Exhibitions But to Make Exhibitions Politically! ; Maria Lactans – Post-Exhibitionary Ruminations: Summer of 2021 ; Bassam El Baroni – Whither the Exhibition in the Age of Finance? Notes towards a Curatorial Practice of Leveraging
boek